Rehabilitacija otrok - Damjan, Hermina (Rehabilitacija (Ljubljana), 2009)
The modern concept of care for children with disabilities includes the obligation of the community to ensure full access to rehabilitation programs in order to achieve the child's social integration and maximal individual development. Family-centered care builds its programs on the partnership between the family and professionals. Modern technology brings advanced methods of medical care and rehabilitation. In spite of that, the child as a whole personality must remain the concern of the modern rehabilitation concept. Modern technology is only a part of support for the maximal quality of life of the child and the family. The society must assure equal opportunities for children with disabilities compared to the healthy population.
Keywords: rehabilitacija; vocational rehabilitation; otroci; child; otroci s posebnimi potrebami; zdravljenje; therapy; družina; family; moderna tehnologija; robotika; navidezna resničnost